VENUS Study: ViEw of HidradeNitis SuppUrativa by PortugueSe General Practitioners - Mendes-Bastos,Pedro (2020)
ABSTRACT Introduction: Hidradenitis suppurativa (HS) is a chronic dermatosis with a large impact in patients’ quality of life and an estimated 7-year delay in diagnosis. The General Practitioner (GP) is usually the first doctor to assist the HS patient. The primary objective of this study is to describe the knowledge and clinical approach of HS by GPs. Material and Methods: A cross-sectional study was conducted, based on the GPs answers to a questionnaire designed to evaluate their knowledge on HS. Results: One hundred eighty seven questionnaires were considered valid for inclusion in the study. The majority (97.3%) of GPs correctly identified HS as the most likely diagnosis when confronted with a typical clinical history of the disease, and 84.5% associated HS with chronicity. The majority (84.0%) of GPs refers these patients, mostly to Dermatology (89.3%). The majority of GPs also considered that a surgical approach may not be curative (94.1%) and 15.0% considered that biological agents might be indicated. We compared the answers of 2 groups: group A, n=100, with <5 years of clinical practice and group B, n=84, with ≥5 years. Group A associated more HS with tobacco use and obesity than group B (p=0.013 and p=0.006, respectively). A multidisciplinary approach was also more frequently selected by group A (p=0.004). Conclusion: This pilot study shows that the view of Portuguese GPs about HS can be improved. There are significant differences concerning knowledge on HS between GPs with less than 5 years of clinical practice and the more experienced ones. This study can help to direct differential future educational actions.